An Open Letter from Past Presidents of the American Nurses Association. Issue 11 (November 2020) - Cipriano, Pamela; Daley, Karen; Patton, Rebecca; Blakeney, Barbara; Foley, Mary; Betts, Virginia Trotter; Cole, Eunice; Nichols, Barbara
Abstract : Eight former ANA presidents urge nurses to consider nursing's values when they vote.